ANALYSIS OF THE EFFECT OF GOOD CORPORATE GOVERNANCE MECHANISM ON FINANCIAL PERFORMANCE ON FAMILY COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Asyriana, Sofia; Maulana, Maulana (International Journal of Multidisciplinary Research and Literature, 2022)
This studys aims to determine the analysis of the effect of good corporate governance mechanisms on the company's financial performance. The sample data obtained were 47 companies for the period 2018-2020 which were associated with 5 research variables, namely 4 independent variables: Independent Board of Commissioners, Institutional Ownership, Managerial Ownership, Audit Committee and 1 dependent variable: Company Financial Performance Measured by Return On Assets (ROA). The data analysis methods used were coefficient of determination test, F statistic test and t statistic test. The results showed that the independent board of commissioners variables, institutional ownership and managerial ownership had no effect on the financial performance assessment as measured by ROA. While the audit committee variable has a significant effect on financial performance as measured by ROA. All variables simultaneously have a significant effect on the assessment of financial performance as measured by ROA